68Ga-FAPI-04 Versus 18F-FDG PET/CT in the Detection of Hepatocellular Carcinoma - Wang, Hao; Zhu, Wenwei; Ren, Shuhua; Kong, Yanyan; Huang, Qi; Zhao, Jun; Guan, Yihui; Jia, Huliang; Chen, Jinhong; Lu, Lu; Xie, Fang; Qin, Lunxiu (Frontiers in Oncology, 2021)
Background: Fibroblast activation protein (FAP) is commonly expressed in activated stromal fibroblasts in various epithelial tumours. Recently, 68Ga-FAPI-04 has been used for tumour imaging in positron emission tomography/computed tomography (PET/CT). This study aimed to compare the diagnostic performances of 68Ga-FAPI-04 PET/CT and 18F-FDG PET/CT in hepatocellular carcinoma (HCC), and to assess factors associated with 68Ga-FAPI-04 uptake in HCC. Materials and methods: Twenty-nine patients with suspiciously HCC who received both 18F-FDG and 68Ga-FAPI-04 PET/CT were included in this retrospective study. The results were interpreted by two experienced nuclear medicine physicians independently. The maximum and mean standardized uptake values (SUVmax and SUVmean) were measured in the lesions and liver background, respectively. The tumour-to-background ratio (TBR) was then calculated as lesion’s SUVmax divided by background SUVmean. Results: A total of 35 intrahepatic lesions in 25 patients with HCC were finally involved in the statistical analysis. 68Ga-FAPI-04 PET/CT showed a higher sensitivity than 18F-FDG PET/CT in detecting intrahepatic HCC lesions (85.7% vs. 57.1%, P = 0.002), including in small (≤ 2 cm in diameter; 68.8% vs. 18.8%, P = 0.008) and well- or moderately-differentiated (83.3% vs. 33.3%, P = 0.031) tumors. SUVmax was comparable between 68Ga-FAPI-04 and 18F-FDG (6.96 ± 5.01 vs. 5.89 ± 3.38, P ˃ 0.05), but the TBR was significantly higher in the 68Ga-FAPI-04 group compared with the 18F-FDG group (11.90 ± 8.35 vs. 3.14 ± 1.59, P ˂ 0.001). SUVmax and the TBR in 68Ga-FAPI-04 positive lesions were associated with tumour size (both P ˂ 0.05), but not the remaining clinical and pathological features (all P ˃ 0.05). Conclusions: 68Ga-FAPI-04 PET/CT is more sensitive than 18F-FDG PET/CT in detecting HCC lesions, and 68Ga-FAPI-04 uptake is correlated mainly with tumour size.